Effects of NPKS on growth, yield and quality of late sown toria varieties (Brassica rapa L. var. toria) under rainfed condition of north-east India - Kumar, Rakesh (Bangladesh Journal of Botany, 2018)
Results on the effect of various levels of NPKS on toria varieties (Brassica rapa var. toria) revealed that the growth attributes (plant height, branches/plant, dry matter/plant) and yield attributes (siliquae/plant, seeds/silique, length of silique and 1000-seed weight), seed, stover and biological yield increased with increasing the levels of NPKS application. Application of 150% RDF, which was at par with 125% RDF but showed significantly superior to 100% RDF and the control. Similarly, the higher economics, nutrient content (NPKS) and uptake, oil, protein content of seed and their yield were also increased with increasing levels of fertilizers (NPKS) up to 150% RDF. Amongst the three toria varieties, TS-38 and TS-36 had significantly higher growth and yield over M-27. Similarly, the economics, nutrient content and their uptake, oil, protein content and their yield were also significantly higher in TS-38 followed by TS-36.